From CEDES to UCLA: significant acts of the university presidents during sixty years of university management (Revista Electrónica REDINE, 2023)
This work presents a synthesis of the university management carried out by the illustrious Presidents of the Universidad Centroccidental “Lisandro Alvarado”, since the creation of the Centro Experimental de Estudios Superiores (CEDES) on September 22, 1962, until today (September 22, 2022). This document describes the most significant academic and/or administrative efforts carried out by Dr. Lorenzo Antonio Vivas (1962-1967), Director-President of the Organizing Commission of CEDES; Dr. Omar Díaz Quiñones, President of the Universidad Experimental de la Region Centro Occidental (UERCO) and subsequently, of the Universidad de la Region Centro Occidental (URCO) (1967-1968); Dr. Argimiro Bracamonte, President of the URCO and the Universidad Centro Occidental (UCO) (1968-1974); Dr. Héctor Ochoa Zuleta, President of the UCO, the Universidad Centro Occidental "Lisandro Alvarado" (UCOLA) and the Universidad Centroccidental “Lisandro Alvarado” (UCLA) (1974-1979 and 1979-1982); Dr. Carlos Zapata Escalona, President of UCLA (1982-1985); Dr. Ricardo García de Longoria, President of UCLA (1985-1986;1986-1990 and 1990-1994); Lic. José Bethelmy, President of UCLA (1994-1998 and 1998-2002); Lic. Francesco Leone, President of UCLA (2002-2006, 2006-2010 and 2010-2017); Dr. Nelly del Valle Velásquez Velásquez, President in charge of UCLA (2017-2020) and Lic. Edgar Alvarado, President in charge of UCLA (2020-2022) The excellent management carried out by the University Presidents from CEDES to UCLA, has been a significant factor in the development of professionals graduated from our Institution, with great both national and international recognition.
Keywords: Dean; CEDES; UERCO; URCO; UCO; UCOLA; UCLA